MENGANALISIS PERAN RUANG TERRBUKA HIJAU TERHADAP KONDISI LINGKUNGAN KOTA AMBON - Ngurmasa Refialy; Robert Oszaer; Yosevita Theodora Latupapua (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2019)
This study aims to analyze the role of Green Open Space on Environmental Protection in Ambon City. The method of data collection is done by collecting primary data in the form of micro climate measurements (temperature and air humidity) at each RTH location. Micro climate data is then processed using microscope office excel, to get the results of comparison tabulations and graphs. After the data tabulation value was obtained statistically analyzed by correlation test. this technique aims to determine the effect of green space on air temperature and green space on air humidity in various types of green open spaces. To analyze the effect of Green Open Space on the preservation of the environment of the city of Ambon, a Spearman correlation correlation tool with Pearson control was performed. The results showed that the results of the microclimate measurements carried out on the Green Path each way Dr. Malaiholo, Pattimura road, Piere Tandean road, Dr. Leimena, shows the air temperature and average humidity of Dr. Malaihollo 32.3 ℃ and RH 68.5%, Pattimura road 33.2 ℃ and RH 61.0%, Jalan Piere Tandean 32.5 ℃ and RH 64.0%, Jalan Dr. Leimena 33.0 ℃ and RH 56.7%. Based on the results of the Convenience Analysis, the four green lines are classified as uncomfortable because the average is in the value of> 27.